Neuronal Cell-type Engineering by Transcriptional Activation - Liu, Songlei; Striebel, Johannes; Pasquini, Giovanni; Ng, Alex H. M.; Khoshakhlagh, Parastoo; Church, George M.; Busskamp, Volker (Frontiers in Genome Editing, 2021)
Gene activation with the CRISPR-Cas system has great implications in studying gene function, controlling cellular behavior, and modulating disease progression. In this review, we survey recent studies on targeted gene activation and multiplexed screening for inducing neuronal differentiation using CRISPRa and open reading frame (ORF) expression. Critical technical parameters of CRISPRa and ORF-based strategies for neuronal programming are presented and discussed. In addition, recent progress on in vivo applications of CRISPRa to the nervous system are highlighted. Overall, CRISPRa represents a valuable addition to the experimental toolbox for neuronal cell-type programming.